Analysis Of The Effectiveness Of A Website As A Tool For Gathering Public Aspirations At The West Java Regional Representative Council Office - Hidayat, Tiara Al Haq; Tricahyono, Dodie (eProceedings of Management, 2023)
With the rapid advancement of technology, changes are constantly taking place. Advances in technology allowhumans to continue to create new things that can benefit humanity. The term digitalization is now a common thingfor the community. People have been innovating a lot to shorten as much as possible the time needed tocomplete a job effectively and efficiently. The era of digitalization is slowly spreading in all directions, makingthe lives of many people more practical. By digitizing government activities, for instance in aspiration taking oronline aspiration, the government can improve public services and serve the community easily, openly andquickly. By using qualitative methods, this research will get results from observation and interview techniques.Observations were made by the author directly in the field, and followed a series of activities by members of theDPRD. The results of this study are expected to inspire prospective researchers to further research the same topicso that the research does not stop here. The results of this study are also expected to help the Secretariat of theDPRD of West Java Province to improve the current aspiration-taking system in order to increase theeffectiveness and optimization of the system.Keywords-government, digitalization, online aspiration